Adenosine 5'-triphosphate-linked transhydrogenase in cytoplasmic membranes of colicin-treated and untreated Escherichia coli. - Sabet, S F (1977)
The adenosine 5'-triphosphate (ATP)-linked transhydrogenase reaction, present in the particulate fractions of Escherichia coli, was previously shown to be inhibited in these fractions when the bacteria were treated with colicins K or El. The purpose of this study was to characterized the ATP-linked transhydrogenase reaction and the colicin-caused inhibition of the reaction in purified cytoplasmic membranes. Particulate fractions from bacteria treated or untreated with colicins were separated on sucrose gradients into cell wall membrane and cytoplasmic membrane fractions. The ATP-linked transhydrogenase reaction was found to be exclusively associated with the cytoplasmic membrane fractions. The reaction was inhibited by carbonylcyanide m-chlorophenlhdrazone, dinitrophenol, N,N'-dicyclohexylcarbodiimide, and trypsin. Although the cytoplasmic membrane fractions were purified from the majoriy of the cell wall membrane and its bound colicins, they showed the inhibitory effects of colicins K and El on the ATP-linked transhydrogenase reaction. The inhibition of ATP-linked transhydrogenase reaction induced by the colicin could not be reversed by subjection the isolated membranes to a variety of physical and chemical treatments. Cytoplasmic membranes depleted of energy-transducing adenosine triphosphatase ATPase) complex (coupling factor) lost the ATP-linked transhydrogenase activity. The ATPase complexes isolated from membranes of bacteria treated or untreated with colicins El or K reconstituted high levels of ATP-linded transhydrogenase activity to depleted membranes of untreated bacteria. The same ATPase complexes reconstituted low levels of activity to depleted membranes of the treated bacteria.